2013
DOI: 10.3389/fgene.2013.00268
|View full text |Cite
|
Sign up to set email alerts
|

EMR-linked GWAS study: investigation of variation landscape of loci for body mass index in children

Abstract: Common variations at the loci harboring the fat mass and obesity gene (FTO), MC4R, and TMEM18 are consistently reported as being associated with obesity and body mass index (BMI) especially in adult population. In order to confirm this effect in pediatric population five European ancestry cohorts from pediatric eMERGE-II network (CCHMC-BCH) were evaluated.Method: Data on 5049 samples of European ancestry were obtained from the Electronic Medical Records (EMRs) of two large academic centers in five different ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 38 publications
2
43
0
1
Order By: Relevance
“…One SNP in this gene was nominally associated with RMR in the present study, although not reaching robust statistical significance thresholds ( p -value = 3.0 × 10 −4 ). Other genes in this region have also been implicated in differential adipose deposition ( LARGE [78] and HMGXB4 [34]) and fat mass (near ODF3B ) [25], and electronic medical record-defined BMI in children ( APOL5 ) [79], suggesting that our study has detected a biological relationship with energy balance or storage in this region, consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…One SNP in this gene was nominally associated with RMR in the present study, although not reaching robust statistical significance thresholds ( p -value = 3.0 × 10 −4 ). Other genes in this region have also been implicated in differential adipose deposition ( LARGE [78] and HMGXB4 [34]) and fat mass (near ODF3B ) [25], and electronic medical record-defined BMI in children ( APOL5 ) [79], suggesting that our study has detected a biological relationship with energy balance or storage in this region, consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…CCK is a satiety hormone and has been associated with obesity. CCK rs8192472 specifically has been reported as being associated with obesity and was identified as a predictor of obesity in GWAS [29]. We found that CCK rs8192472 was marginally associated with breast cancer risk among women with high IA ancestry after adjustment for multiple comparisons (data not shown, OR = 0.55, 95% CI 0.33–0.91; p = 0.02 and p adj 0.059).…”
Section: Discussionmentioning
confidence: 66%
“…Thus, integrating both clinical laboratory measurements and diagnosis codes present powerful approaches for understanding genetic variants that show similar associations with both data types obtained from an EHR 3 . The majority of association studies that use quantitative traits derived from an EHR as phenotypes use either mean/median values 3,6 or most recent measurements 7 . While this approach has been successful, utilizing only mean/median values limits the understanding of these traits by neglecting the variability over time that may be present in an individual patient's clinical history.…”
Section: Introductionmentioning
confidence: 99%